Digital Platform for Pediatric Mental Health Support During Armed Conflicts: Development and Usability Study - Hila Segal; Arriel Benis; Shirley Saar; Iris Shachar-Lavie; Silvana Fennig (JMIR Formative Research)
Abstract BackgroundThe prevalence of mental health disorders among children and adolescents presents a significant public health challenge. Children exposed to armed conflicts are at a particularly high risk of developing mental health problems, necessitating prompt and robust intervention. The acute need for early intervention in these situations is well recognized, as timely support can mitigate long-term negative outcomes. Pediatricians are particularly suited to deliver such interventions due to their role as primary health care providers and their frequent contact with children and families. However, barriers such as limited training and resources often hinder their ability to effectively address these issues. ObjectivesThis study aimed to describe the rapid development of a digital mental health tool for community pediatricians, created in response to the urgent need for accessible resources following the October 7th terror attack in Israel. The goal was to create a comprehensive resource that addresses a wide range of emotional and behavioral challenges in children and adolescents, with a particular focus on those affected by armed conflict and significant trauma exposure. In addition, the study aimed to evaluate the platform’s usability and relevance through feedback from primary users, thereby assessing its potential for implementation in pediatric practice. MethodsA digital platform was developed using a collaborative approach that involved pediatricians and mental health professionals from various hospital clinics. The initial framework for the modules was drafted based on key emotional and behavioral issues identified through prior research. Following this, the detailed content of each module was cocreated with input from specialized mental health clinics within the hospital, ensuring comprehensive and practical guidance for community pediatricians. A focus group of 7 primary users, selected for their relevant hospital and community roles, provided feedback on the platform’s user experience, content relevance, and layout. The evaluation was conducted using a structured questionnaire complemented by qualitative comments. ResultsFifteen detailed modules were created, each providing information, including anamnesis, initial intervention strategies, parental guidance, and referral options. The focus group feedback demonstrated high satisfaction, indicating a very good user experience (mean 4.57, SD 0.53), content relevance (mean 4.71, SD 0.48), and layout suitability (mean 4.66, SD 0.52). Specific feedback highlighted the value of concise, actionable content and the inclusion of medication information. Participants expressed a strong willingness to regularly use the platform in their practice (mean 4.40, SD 0.53), suggesting its potential for broad application. ConclusionsThis study demonstrates the effectiveness of a collaborative development process in creating a digital tool that addresses the mental health needs of children in crisis situations. The positive feedback from pediatricians indicated that the platform has the potential to become a valuable resource for early recognition, crisis intervention, and parental support in community pediatric settings. Future research will focus on broader implementation and assessing the platform’s impact on clinical outcomes.